Social science monitoring as a management tool for directing the benefits of new agricultural technology to the poor - Romanoff, S.A. (International Irrigation Management Institute, 1989)
The study reported here monitored the introduction of an agroindustrial technology for processing the starchy roots of cassava for animal feed. CIAT transferred the technology from Thailand to Colombia, where groups of farmers began building drying plants under the guidance of the Colombian Government's Integrated Rural Development Program (DRI). Based on data gathered by DRI agencies and the author, this paper discusses management decisions at different levels of the project, and how those decisions directed or could have directed the benefits of the project to particular beneficiaries. The analytical approach of this paper follows a simple paradigm: a variable that can be manipulated by a manager is correlated with some beneficiary characteristic. A conclusion is then drawn about how the decisions did or could skew benefits to the poor. This method of analysis is fairly generalizable because monitoring and evaluation units are often appended to development projects. Results of this study and its monitoring approach are being used in Colombia. In Ecuador also, both the project and the pilot monitoring activity have been replicated, and some of the lessons from the Colombian case have been applied. The paper concludes with a note on the Ecuadorian experience and the limits of management and monitoring. (AS (extract))